Effects of Warfarin Nomogram in Initial Phase Warfarin Patients at Charoenkrung Pracharak Hospital - Pimpa, Dhanupom; Sujarit, Alisara; Charoensri, Nisarat (Interprofessional Journal of Health Sciences, 2024)
Most physicians initiate and adjust warfarin dose based on International Normalized Ratio (INR)and their clinical judgment. This study was conducted to investigate the effects of using warfarin nomograms in patients initiated warfarin at Charoenkrung Pracharak hospital. This study was a randomized controlled trial involving patients who started using warfarin while hospitalized at Charoenkrung Pracharak hospital from August to November 2023. The experimental group received the initiation and dosage adjustments of warfarin using the warfarin nomograms, while the control group had their warfarin initiation and dosage adjustments based on the physician’s clinical judgment, analyzing the proportion of patients who achieved an INR between 2.0 and 3.0 within 14 days after warfarin initiation. From a total sample of 98 individuals, divided into control (49) and experimental (49) groups, Baseline characteristics of both groups were not significantly different except for gender. The research findings indicated a statistically significant difference between the experimental and control groups concerning the proportion of patients with INR values within the range of 2.0 to 3.0 within 14 days after receiving warfarin (44.9% and 24.5%, respectively, p=0.034). The use of warfarin nomograms for initiating and adjusting dosages allows patients to achieve their target INR range more effectively than starting and adjusting doses solely based on physician judgment. Additionally, the safety of using warfarin nomograms does not significantly differ from initiating and adjusting doses solely based on physician judgment.